The quest for meaning : friends of wisdom from Plato to Levinas - Peperzak, Adriaan Theodoor, 1929- (UPSO - Fordham University Press E-Books., 2003)
Adriaan Peperzak has for many years explored the connections between philosophy, ethics, religion and human experience. An expert on Hegel, Heidegger and Levinas, he here offers a gathering of influences on his own work as guides to uses of philosophy in our search for sense and meaning.